Characterization of t-loop formation by TRF2 - Timashev, Leonid A. (Nucleus, 2020)
T-loops are thought to hide telomeres from DNA damage signaling and DSB repair pathways. T-loop formation requires the shelterin component TRF2, which represses ATM signaling and NHEJ. Here we establish that TRF2 alone, in the absence of other shelterin proteins can form t-loops. Mouse and human cells contain two isoforms of TRF2, one of which is uncharacterized. We show that both isoforms protect telomeres and form t-loops. The isoforms are not cell cycle regulated and t-loops are present in G1, S, and G2.  Using the DNA wrapping deficient TRF2 Topless mutant, we confirm its inability to form t-loops and repress ATM. However, since the mutant is also defective in repression of NHEJ and telomeric localization, the role of topological changes in telomere protection remains unclear.  Finally, we show that Rad51 does not affect t-loop frequencies or telomere protection. Therefore, alternative models for how TRF2 forms t-loops should be explored.